Current landscape and tailored management of immune-related adverse events - Liu, Wenhui; Luo, Zhiying; Liu, Yiping; Sun, Bao (Frontiers in Pharmacology, 2023)
Unprecedented advances have been made in immune checkpoint inhibitors (ICIs) in the treatment of cancer. However, the overall benefits from ICIs are impaired by the increasing incidence of immune-related adverse events (irAEs). Although several factors and mechanisms have been proposed in the development of irAEs, there is still incomprehensive understanding of irAEs. Therefore, it is urgent to identify certain risk factors and biomarkers that predict the development of irAEs, as well as to understand the underlying mechanisms of these adverse events. Herein, we comprehensively summarize the state-of-the-art knowledge about clinical features and the related risk factors of irAEs. Particularly, we also discuss relevant mechanisms of irAEs and address the mechanism-based strategies, aiming to develop a tailored management approach for irAEs.